The link between adverse childhood experiences, emotional intelligence and alexithymia : a comparative study between a sample of offenders and the general population - Redondo, Tatiana Gonzaga (My University, 2023)
Background: Individuals with a history of adverse childhood experiences (ACEs) are likely to display alexithymia and are more prone to engage in criminal behaviors, Emotional intelligence (EI) also plays a significant role in aggression and criminal behavior. Objectives: This study intends to a) assess the relationship between ACEs and alexithymia; b) assess the relationship between ACEs and EI; c) to compare a sample of offenders with a sample of the general population in the variables under study. Methods: The sample comprised a general population and an offender population. This research included a sample of 245 individuals from the general and offender population, with ages ranging from 18 to 68. The participants responded to the Adverse Childhood Experiences Questionnaire (ACEs; Felitti, 1998; Portuguese version, Pinto et al., 2014), that examines various adverse experiences during childhood; the Toronto Alexithymia Scale (TAS-20; Taylor et al.,1992; Portuguese version, Praceres et al., 2000), which assesses characteristics of alexithymia; and the Wong Law Emotional Intelligence Scale (WLEIS; Wong & Law, 2002), which measures emotional intelligence. Results: In the first study, it was observed the offender population revealed higher scores of ACEs and TAS than the general population. In the general population were found statistically significant positive correlations between difficulty identifying feelings, emotional neglect and ACE; statistically significant positive correlations between difficulty describing feelings, and emotional neglect; statistically significant positive correlations between externally oriented thinking, emotional abuse, emotional neglect, and parental divorce; statistically significant positive correlations between emotional neglect and TAS. Within the offender population they were found statistically significant positive correlations between difficulty identifying feelings and emotional neglect; statistically significant positive correlations between difficulty identifying feelings, violence exposure, incarcerated family member and ACE; statistically significant positive correlations between alexithymia and emotional neglect. The findings indicated that individuals within the offender population obtained significantly higher scores of ACEs compared to the general population sample, as well as the total score of ACEs. Additionally, the results revealed that the offender population presents higher scores regarding alexithymia, particularly, in the externally oriented thinking dimension. In the second study, the offender population exhibited higher scores of ACEs and EI when compared to the general population. In the general population it was revealed statistically significant negative correlations between self-emotions appraisal and emotional neglect; statistically significant negative correlations between emotional abuse, physical abuse, sexual abuse, emotional neglect, and regulation of emotions; a statistically significant negative correlations were also found between physical abuse, emotional neglect and WLEIS. In the offender population it was found a statistically significant positive correlations between others’ emotions appraisal and emotional neglect. Conclusion: The findings empathize the importance of developing prevention strategies, to reduce the prevalence of ACEs in the population, both inmate and general population. Further research needs to be conducted including a wider homogeneous sample, to better understand the intricate interactions between ACEs, alexithymia, emotional intelligence and subsequent criminal behavior.

Enquadramento: Os indivíduos que vivenciaram experiências adversas na infância são mais suscetíveis de apresentar alexitimia e são mais propensos a envolver-se em comportamentos criminosos. A inteligência emocional (IE) também desempenha um papel significativo na agressão e no comportamento criminoso. Objetivos: Este estudo pretende: a) avaliar a relação entre as experiências adversas na infância e a alexitimia; b) avaliar a relação entre as experiências adversas na infância e a inteligência emocional; c) comparar uma amostra de ofensores com uma amostra da população geral nas variáveis em estudo. Método: A amostra foi constituída por participantes da população geral e por uma amostra de ofensores, com idades compreendidas entre os 18 e os 68 anos. Os participantes responderam ao Adverse Childhood Experiences Questionnaire (ACEs; Felitti, 1998; Portuguese version, Pinto et al., 2014), que examina diversas experiências adversas durante a infância e a sua natureza; Escala de Alexitimia de Toronto (TAS-20; Taylor et al.,1992; Portuguese version, Praceres et al., 2000), que avalia as características da alexitimia; e a Escala de Inteligência Emocional de Wong e Law (WLEIS; Wong & Law, 2002), que mede a inteligência emocional. Resultados: No primeiro estudo, na população geral foram verificadas correlações positivas estatisticamente significativas entre a dificuldade em identificar sentimentos, a negligência emocional e ACE; dificuldade em descrever sentimentos e negligência emocional; e pensamento orientado para o exterior, abuso emocional, negligência emocional e divórcio dos pais. Na população de ofensores, foram encontradas correlações negativas estatisticamente significativas entre a dificuldade em identificar sentimentos e a negligência emocional; correlações positivas estatisticamente significativas entre a dificuldade em identificar sentimentos, exposição à violência, membro da família encarcerado e ACE; e a alexitimia e negligência emocional. Os indivíduos da população de ofensores obtiveram pontuações significativamente mais elevadas de ACEs e alexitimia, particularmente na dimensão do pensamento orientado para o exterior. em comparação com a amostra da população geral. No segundo estudo, na população geral verificaram-se correlações negativas estatisticamente significativas entre a negligência emocional e a avaliação das suas emoções; e entre os maus tratos emocionais, os maus tratos físicos, os maus tratos sexuais, a negligência emocional e a regulação das emoções. Foram também encontradas correlações negativas estatisticamente significativas entre os maus tratos físicos, a negligência emocional e a WLEIS. Na população de ofensores verificaram-se correlações positivas estatisticamente significativas entre a avaliação das emoções dos outros e a negligência emocional. Conclusão: Os resultados demonstram a importância do desenvolvimento de estratégias de prevenção, para reduzir a prevalência de experiências adversas na infância na população, tanto nos ofensores como na população em geral. É necessário realizar mais investigação, incluindo uma amostra homogénea mais ampla, a fim de compreender melhor as interações particulares entre as experiências adversas na infância, a alexitimia, a inteligência emocional e o comportamento criminoso subsequente.
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz
Keywords: Adverse childhood experiences; ACEs; Alexithymia; TAS; Emotional intelligence; EI; General; Offenders